The role of social disparity, religiosity, and technology adoption in shaping infaq intention in Indonesia - Apip; Dul Muid; Thariq Hanifan Abdurrabbi (Journal of Islamic Economics Management and Business (JIEMB), 2025)
This study examines the influence of social disparity and asymmetric information on individuals’ intention to give infaq in Indonesia. The research aims to understand how socioeconomic status, religiosity, empathy, residential environment, and technology adoption shape infaq behavior in a digital context. Using a quantitative approach with multiple regression analysis on survey data, the study finds that income level, religiosity, and technology adoption significantly affect infaq intention, while cultural norms, empathy, and residential environment show no direct impact. Moreover, technology adoption mediates the relationship between residential environment and infaq intention, highlighting the growing importance of digital facilitation in charitable giving. These findings contribute to Islamic behavioral economics by revealing that infaq motivation is increasingly driven by internal religiosity and technological accessibility rather than traditional social influences. The study provides practical implications for policymakers and Islamic financial institutions to strengthen digital infrastructure, promote online infaq platforms, and enhance financial literacy to foster sustainable philanthropic participation.